2011
DOI: 10.1007/s10943-011-9532-2
|View full text |Cite
|
Sign up to set email alerts
|

Kansas Physician Assistants’ Attitudes and Beliefs Regarding Spirituality and Religiosity in Patient Care

Abstract: Research indicates patients want to discuss spirituality/religious (S/R) beliefs with their healthcare provider. This was a cross-sectional study of Kansas physician assistants (PA) regarding S/R in patient care. Surveys included questions about personal S/R beliefs and attitudes about S/R in patient care. Self-reported religious respondents agreed (92%) they should be aware of patient S/R; 82% agreed they should address it. Agreement with incorporating S/R increased significantly based on patient acuity. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
5
0
2
Order By: Relevance
“…These results may be explained by several factors, including the higher levels of religiosity in the Brazilian nursing students. Previous studies have shown that most religious persons tend to be more prone to address and be aware of patients' spiritual and religious issues (Berg et al., ; Lucchetti et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be explained by several factors, including the higher levels of religiosity in the Brazilian nursing students. Previous studies have shown that most religious persons tend to be more prone to address and be aware of patients' spiritual and religious issues (Berg et al., ; Lucchetti et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that most religious persons tend to be more prone to address and be aware of patients' spiritual and religious issues (Berg et al, 2013;Lucchetti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is a variation in physician beliefs about the relevance of religion/spirituality for patient recovery. 53 In a survey of 2000 practising HCPs, only 1% of them considered that they spend too much time on religiosity/spirituality conversations, 38% that they spend too little time and 61% “the right” amount of time. 54 More specifically, reasons reported by physicians for not addressing spiritual issues include lack of time or training, and difficulty in identifying the patients who would welcome spiritual discussions.…”
Section: Are Hcps Educated About Spirituality?mentioning
confidence: 99%
“…As noted above, several studies have suggested that most patients want their health care providers to address their R/S concerns . In a survey of 75 patients and 339 cancer physicians and nurses, Phelps et al found that the majority of patients (77.9%), physicians (71.6%), and nurses (85.1%) believed that routine spiritual care would have a positive impact on patients, but that only 25% of patients had previously received spiritual care.…”
Section: Spirituality In the Experience Of Medical Decision‐makers Smentioning
confidence: 99%